Rehabilitation Through Physical Activity and Sport in Light of the International Classification of Functioning, Disability, and Health-Current Research Perspectives - Isabel Stolz; Isabel Stolz; Elisa Weber; Ruud Vreuls; Volker Anneken (Frontiers Media S.A., 2022)
The implementation of functioning by the World Health Organization (WHO) as the third global health indicator, along with mortality and morbidity, represents a promising advancement for a comprehensive assessment of international health systems and health strategies. The description of a person's health state operationalized by both biological and lived health via functioning provides a holistic picture of an individual's life situation and proved to be successful in building a framework for formulating therapy goals, achievable activities, and participational aspects against the background of an individual's life situation. Furthermore, improving an individual's functional ability and wellbeing could potentially affect the health indicators of morbidity and mortality and will be codable beyond the ICF in ICD-11. This methodological perspective emphasizes the use of ICF applications on the wider and narrower level of international rehabilitation systems and highlights the incorporation of the term functioning in rehabilitation through physical activity and sport. Current research perspectives in applying the ICF and functioning in clinical and rehabilitation practices are discussed and a current explorative study is presented, which applies the holistic orientation of functioning and the biopsychosocial model to the specific case by an individualized sports coaching intervention in rehabilitation. Subsequently, a unifying ICF- oriented language in rehabilitation is considered as a powerful foundation for a consistent international research strategy concerning increased international collaborations and future research perspectives.